Predictive Factors of Fatal Bleeding in Pediatric Acute Promyelocytic Leukemia (APL) - Rabiha Manzoor; Fozia Sayed Rasool; Qurratulain Ali; Fahd Rashid; Ajaz Ahmed; Iqra Tariq (Pakistan Journal of Medicine and Dentistry)
Background:  Pediatric APL has a higher bleeding risk but better outcomes. This study aimed to identify predictors of fatal bleeding in pediatric APL to optimize early interventions and improve survival in Pakistan.